PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN HUTANG, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Students' Journal of Accounting and Banking, 2014)
This study aims to determine the effect of managerial ownership, institutional ownership, debt policy, profitability, and firm size on dividend policy. The population in  this study is the manufacturing companies listed on the stock exchanges of Indonesia from 2009-2012. The samples in this study were taken by the method of pooling the data. Data were analyzed by using the kolmogorov-smirnov test for normality, the classical assumption, koofisiendeterminasi test, F-test and test hypotheses. The results of this study are significant positive effect of managerial ownership on dividend policy, institutional ownership is not a significant positive effect on dividend policy, debt policy is not a significant positive effect on dividend policy, Profitability significant positive effect on dividend policy, significant positive effect of firm size on dividend policy. Keywords: dividend policy, managerialownership, institutional ownership, debt policy, profitability, size ofthe company